HPLC‐TBARS‐EVSC (high‐performance liquid chromatography–thiobarbituric acid reactive substances–ex vivo stratum corneum) protocol: Selection of the subjects and approach to present the results - Marques, Gabriela de Argollo; Hiraishi, Camila Faustino; Macedo, Pedro Ivo de Souza; Pinto, Claudineia Aparecida Sales de Oliveira; Gregório, João; Rosado, Catarina; Velasco, Maria Valéria Robles; Baby, André Rolim (International journal of cosmetic science, 2023)
Nowadays, it is recognized the need for improved safety and efficacy protocols to evaluate the human stratum corneum (SC) and its interaction with topical and cosmetic formulations by minimally or non-invasive methodologies. The aim of our research work was to streamline the HPLC-TBARS-EVSC (high-performance liquid chromatography-thiobarbituric acid reactive substances-ex vivo stratum corneum) methodology, by exploring the results of a group of 18 subjects. The study included nine women and nine men aged between 19 and 57 years old with phototypes from II to V. Sites in the forearm of each volunteer were randomly delimited, and the SC was collected by tape stripping. HPLC was used to quantify the MDA-TBA (malondialdehyde-thiobarbituric acid) adduct from the tape-stripped SC, irradiated and not by an ultraviolet (UV) simulator chamber. Observing the findings of our present investigation, and the statistical approach applied, the use of the ratio between the treatment site and control would be an adequate strategy to better discriminate and evaluate the results. Additionally, an optimal selection of the volunteers to respond specifically to the purpose of the ex vivo assay also can be considered advantageous. It seemed that in future studies focusing on the impact of SC UV-induced lipid peroxidation, determined by the HPLC-TBARS-EVSC, the most suitable subjects are females aged less than 35 years old, with phototype II.